The Postmodern 'Sublime'in Orhan Pamuk's Texts of Innocence - Arikan, Seda (Rector Ciu Cyprus Int Univ, 2023)
Orhan Pamuk published The Museum of Innocence in 2008, two years after getting his title of the first Turkish Nobel laureate. He opened the city museum named '' Museum of Innocence '' four years after the publication of this novel, which he had dreamed of collecting the objects to be exhibited for many years. In the same year, he published a catalogue titled The Innocence of Objects (2012) for this museum in which Pamuk writes about the objects, their relations to his life and his city Istanbul. The documentary film on this city museum, Innocence of Memories (2015), is shot in a collaboration between Pamuk and British director Grant Gee. Finally, a retrospective book titled The Innocence of Memories-which includes the screenplay, the conversation between the author and the director, and selected frames of this film-was published in 2016. All these written and visual texts by Pamuk, which are preferred to be named The Texts of Innocence in this study, open the way for an interplay and intertextuality re-represented by the spiral metaphor. This paper suggests, based on this metaphor that signifies an ' unwinding path ' going through all these narratives, Orhan Pamuk produces the dynamics of the sublime that is related to presenting the unpresentable, free play, aesthetic formation, and the gaze of the perceiver in the postmodernist era. In this sense, this study aims to trace the postmodern dynamics of the sublime, turning around a set of objects presented and (re)presented to the reader, the museum-goer, and the audience within the fiction, the fictionalized non-fiction, and visual art narratives by Orhan Pamuk.
Orhan Pamuk’un MasumiyetMetinleri’nde Postmodern ‘Yüce’
Keywords: Orhan Pamuk; The Museum of Innocence; postmodern sublime; object representation